Speech Act Theory and Deconstruction - Halion, Kevin (My University, 1989)
In this dissertation I examine a distinction made in Speech Act Theory between normal uses of language and uses of language that are said to be parasitic on them. Fictional, theatrical, comedic and metaphoric uses of language may be said to be parasitic on normal language in so far as their intelligibility requires a prior grasp of the rules or conventions of normal language such as is used in everyday cases of asserting, promising, marrying and ordering, for instance.
Jacques Derrida argued that uses of language could not be determined as exclusively either normal or parasitic and that thus such a distinction could not be made. That is, he argued that it was not possible to make a distinction between fictional promises and real life promises, for instance; or between literal uses of words and metaphorical uses. I show that the distinction can be made and that, although uses of language cannot be determined as exclusively either normal or parasitic in the work of J. L. Austin, they can be in that of John R. Searle.
In arguing for this thesis, I show how Searle, in his attempt to defend Austin and Speech Act Theory against Derrida's criticisms, failed to appreciate many aspects of Derrida's work and thus misconstrued his critique and defended Austin and Speech Act Theory against somewhat of a straw man.
Keywords: speech; act theory; parasitic speech; normal speech